1980
DOI: 10.4049/jimmunol.124.1.461
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of lymphocyte responsiveness in early experimental syphilis. II. Nature of cellular infiltration and Treponema pallidum distribution in testicular lesions.

Abstract: The nature of the cellular infiltration and the distribution of Treponema pallidum during rabbit testicular infection were examined by immunofluorescence and light microscopy. Low numbers of treponemes are demonstrable in the perivascular regions on day 3 post-infection. On days 6, 10, and 13, large numbers of organisms are found in the interstitial spaces. The treponemes do not appear to invade the walls or lumina of the seminiferous tubules, although tubular atrophy is obvious. On days 17, 24 and 31, trepone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1983
1983
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The attenuation of lesion progression induced by our tri-antigen vaccine is the result of careful study concerning the type of immune response that is needed to limit T. pallidum proliferation at the challenge site. Based on our earlier studies, we hypothesized that a DTH response is responsible, along with opsonic antibody, for the clearance of T. pallidum from healing primary infections, with T lymphocytes producing IFNγ to activate macrophages for phagocytosis and killing of opsonized T. pallidum [ 48 , 49 ]. In further studies, we observed that the appearance of clinical DTH at challenge sites correlated with subsequent attenuation of lesion progression [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The attenuation of lesion progression induced by our tri-antigen vaccine is the result of careful study concerning the type of immune response that is needed to limit T. pallidum proliferation at the challenge site. Based on our earlier studies, we hypothesized that a DTH response is responsible, along with opsonic antibody, for the clearance of T. pallidum from healing primary infections, with T lymphocytes producing IFNγ to activate macrophages for phagocytosis and killing of opsonized T. pallidum [ 48 , 49 ]. In further studies, we observed that the appearance of clinical DTH at challenge sites correlated with subsequent attenuation of lesion progression [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mature DCs migrate to lymph nodes where they present treponemal antigens to T cells, inducing antigen-specific T cells responses. These T cells can be detected in secondary lymphoid organs of infected animals three days post-infection and progressively accumulate at the infection site (64)(65)(66), coinciding with maximal TPA burden (67,68). Rabbits infected with TPA showed a rapid hyperplasia of T cell zones in secondary lymphoid organs (lymph node and spleen) (38, 66).…”
Section: Infection Course and Immune Responsementioning
confidence: 99%